A deformable polycrystalline zeolite membrane and preparation method thereof
By texturing nanozeolites on the PTFE base film and performing secondary growth, a polycrystalline zeolite film was prepared, which solved the problem of incompatibility of the mechanical properties of the zeolite molecular sieve film and organic carriers, achieved high flexibility and high separation selectivity of the film, and reduced production costs.
Patent Information
- Application Number
- CN202410848374.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-06-27
AI Technical Summary
The existing zeolite molecular sieve membranes are difficult to compatible with flexible organic carriers due to their strong brittleness, which leads to the membrane being prone to cracking, limiting their industrial applications.
By texturing nanozeolites on the PTFE base film, zeolite-doped PTFE (seed) is prepared by electrospinning technology, and then secondary growth is carried out to form a polycrystalline zeolite film to improve the flexibility and binding force of the film.
The prepared polycrystalline zeolite film has excellent tensile strength and flexibility, strong bonding force between the carrier layer and the film layer, high separation selectivity, and reduced production cost, making it suitable for industrial production.
Smart Images

Figure HDA0004916244170000011 
Figure HDA0004916244170000012 
Figure HDA0004916244170000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane synthesis, and in particular relates to a deformable polycrystalline zeolite membrane and a preparation method thereof. Background Art
[0002] Zeolite molecular sieve membranes have been widely studied for the efficient separation of mixed systems such as various gases and liquids due to their uniform molecular-level pore size, excellent thermal stability and chemical stability. Although zeolite molecular sieve membranes have shown good industrial application prospects in the fields of natural gas decarbonization and organic solvent dehydration, their large-scale promotion and application still face the following challenges: Since zeolite molecular sieve membranes are very brittle, they are usually prepared on porous alumina carriers with greater strength to improve the mechanical strength of the membrane. However, due to the very expensive price of alumina carriers, the cost of using zeolite molecular sieve membranes remains high, much higher than the current organic membrane materials. In addition, the packing density of the zeolite molecular sieve membrane supported by the common porous alumina tube is relatively low, resulting in huge processing costs for the membrane assembly of the zeolite molecular sieve membrane. Although the packing density of the zeolite molecular sieve membrane supported by the hollow fiber-shaped porous alumina tube can be improved to a considerable extent, it is not conducive to practical industrial applications due to the weak mechanical strength of the carrier and the brittle molecular sieve membrane layer.
[0003] Based on the above technical problems, zeolite molecular sieve membranes are greatly restricted in practical industrial applications. Summary of the invention
[0004] The purpose of the present invention is to provide a deformable polycrystalline zeolite membrane and a preparation method thereof for the first time; the membrane prepared by the method has excellent tensile strength and flexibility, which is due to the distribution of nanoparticles between the membranes, which increases the performance of PTFE itself. At the same time, after the membrane is formed, the interlayer force between the membrane becomes larger, the carrier layer and the membrane layer have strong bonding force, and the separation selectivity is high. Compared with the conventional zeolite molecular sieve membrane supported by an inorganic carrier, the preparation process of the zeolite molecular sieve polycrystalline membrane is simple, the production cost is greatly reduced, and it is easy to carry out industrial production.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A deformable polycrystalline zeolite membrane and a preparation method thereof, comprising the following steps:
[0007] S1, at room temperature and pressure, under stirring, the nano-zeolite is fully mixed with the PTFE emulsion and the PEO aqueous solution, and the nano-zeolite is spun on the PTFE substrate membrane by using the electrospinning technology to obtain the zeolite-doped PTFE (seed);
[0008] S2: adding the secondary growth liquid of nano zeolite to the zeolite-doped PTFE (seed), and obtaining a molecular sieve membrane based on PTFE through symbiosis, that is, the polycrystalline zeolite membrane or the zeolite molecular sieve membrane.
[0009] The seed refers to a seed crystal.
[0010] Compared with the commonly used porous alumina carrier, the cost of polytetrafluoroethylene is much lower, and the electrospinning technology is mature and easy to produce industrially. Therefore, electrospinning separation membranes have huge cost advantages in practical application and promotion. However, since the mechanical properties of flexible organic carriers are not compatible with the brittle zeolite molecular sieve membrane layer, the zeolite molecular sieve membrane synthesized on the organic carrier is very easy to crack, and it is very challenging to obtain high-quality zeolite membranes.
[0011] Based on this, improving the mechanical properties of the membrane layer and making it relatively compatible with the mechanical properties of the organic carrier is an important way to improve the performance of the zeolite molecular sieve membrane supported by the organic carrier.
[0012] The present invention adds nano zeolite to PTFE solution and PEO solution, and after being fully dispersed, the nano zeolite is spun on the PTFE substrate membrane by an electrostatic spinning process to obtain zeolite-doped PTFE (seed), and then the seed membrane is symbiotically prepared into a zeolite molecular sieve membrane, i.e., a polycrystalline zeolite membrane. The polycrystalline membrane prepared by this method has nanoparticles distributed in the zeolite molecular sieve membrane layer, which greatly improves the flexibility of the molecular sieve membrane layer and the binding force with the organic carrier, thereby making it compatible with the organic carrier, and also greatly reduces the interlayer defects between the molecular sieves, greatly improving the separation selectivity of the membrane.
[0013] The method of the present invention can prepare a polycrystalline membrane that makes the mechanical properties of a brittle molecular sieve membrane layer and a flexible organic carrier compatible. The membrane is a deformable flexible membrane with extremely excellent tensile properties and elastic modulus. It is not easy to crack during actual use, which effectively improves the performance and service life.
[0014] The invention effectively overcomes the technical defect in the prior art that the synthesized zeolite molecular sieve membrane is very easy to crack due to the incompatibility of the mechanical properties of the flexible organic carrier and the brittle zeolite molecular sieve membrane layer.
[0015] In addition, the above-mentioned zeolite molecular sieve membrane has a simple preparation process, excellent separation performance, strong adaptability to organic carriers, and is easy to be industrially scaled up and applied.
[0016] As one possible embodiment of the present application, in step S1, the molar ratio of the nano zeolite to the PTFE emulsion and the PEO aqueous solution is 1:(1-1.5):1.
[0017] Wherein, in step S1, the step of fully mixing the nano zeolite with the PTFE emulsion and the PEO aqueous solution is as follows:
[0018] A polyethylene oxide aqueous solution with a solid content of 15 wt% is prepared and allowed to stand for degassing; thereafter, a polytetrafluoroethylene emulsion with a solid content of 60 wt% is uniformly dispersed in the polyethylene oxide solution under the action of magnetic stirring, and after stirring for 3 hours, a polytetrafluoroethylene / polyethylene oxide spinning solution is obtained, i.e., a mixed emulsion is obtained; finally, nano zeolite particles are uniformly dispersed in the mixed emulsion to obtain a spinning mixed solution.
[0019] As one of the embodiments of the present application, in order to effectively ensure that the nano zeolite can be fully mixed with the PTFE emulsion and the PEO aqueous solution, the temperature and time for full mixing in step S1 are limited, that is, in step S1, the temperature for full mixing is 25-30°C and the time is 24h.
[0020] As one of the embodiments of the present application, the process parameters of the electrospinning are as follows: voltage of 25 kV, humidity of 50%, temperature of 25-30° C., and normal pressure.
[0021] The present invention can make the prepared membrane structure and pore size distribution more uniform by limiting the parameters of the electrospinning process, greatly improving the flexibility of the membrane layer and the bonding force with the carrier, as well as the tensile strength of the zeolite polycrystalline membrane.
[0022] As one possible embodiment of the present application, in S1, the nano zeolite is an MFI type molecular sieve, a FAU type molecular sieve or an LTA type molecular sieve;
[0023] When the nano zeolite is an MFI type molecular sieve, the zeolite doped with PTFE (seed) is PTFE-MFI (seed), and the molecular sieve membrane based on PTFE is a PTFE-MFI molecular sieve membrane;
[0024] When the nano zeolite is a FAU type molecular sieve, the zeolite doped with PTFE (seed) is PTFE-FAU (seed), and the molecular sieve membrane based on PTFE is a PTFE-FAU molecular sieve membrane;
[0025] When the nano zeolite is an LTA type molecular sieve, the selected molecular sieve is a NaA molecular sieve, the zeolite doped with PTFE (seed) is PTFE-NaA (seed), and the molecular sieve membrane based on PTFE is a PTFE-NaA molecular sieve membrane.
[0026] A large number of experiments have proved that the above three molecular sieves can be successfully prepared into deformable flexible polycrystalline membranes according to the process of the present invention.
[0027] As one of the possible embodiments of the present application, the particle size of the MFI molecular sieve is 50-100 nm; the particle size of the FAU molecular sieve is 300-500 nm; and the particle size of the NaA molecular sieve is 150-400 nm.
[0028] In addition, the above three molecular sieves have different sizes. The MFI type molecular sieve is a two-dimensional 10-membered ring channel with a pore diameter of 0.54nm; the FAU type molecular sieve is a faujasite type, and is a three-dimensional 12-membered ring channel system with a pore diameter of 0.74nm; the NaA molecular sieve is a three-dimensional 8-membered ring vertical channel with a pore diameter of 0.4nm.
[0029] As one possible embodiment of the present application, when the nano zeolite is an MFI type molecular sieve, the secondary growth liquid of the nano zeolite includes SiO2, NaOH, Al2(SO4)3·18H2O and H2O, wherein the molar ratio of the four is 0.02:0.01:0.0001:1.2;
[0030] When the nano zeolite is a FAU type molecular sieve, the secondary growth liquid of the nano zeolite includes water glass, NaAlO2 and H2O; wherein the molar ratio of the three is 0.01:0.003:2.3;
[0031] When the nano zeolite is NaA molecular sieve, the secondary growth liquid of the nano zeolite includes LuDoxAs-40, Al, NaOH and H2O, wherein the molar ratio of the four is 0.07:0.01:0.6:7.
[0032] The symbiotic process determines the film-forming quality of the molecular sieve membrane layer. The present invention can effectively ensure the successful film formation of the three molecular sieves in the present invention by limiting the components of the secondary growth solution required for the symbiotic process and the dosage relationship between the components, effectively improve the film-forming quality of the molecular sieve membrane layer, and the bonding strength between the molecular sieve and the organic carrier, thereby improving the elastic modulus of the polycrystalline membrane and effectively improving the anti-fission ability of the polycrystalline membrane.
[0033] As one possible embodiment of the present application, in step S2, when the nano zeolite is an MFI molecular sieve, the reaction temperature during symbiosis is 180° C. and the reaction time is 24 hours;
[0034] When the nano zeolite is a FAU type molecular sieve, the reaction temperature during the symbiosis is 100°C and the time is 48h;
[0035] When the nano zeolite is NaA molecular sieve, the reaction temperature during the symbiosis is 60° C. and the reaction time is 48 hours.
[0036] In step S1, the prepared zeolite-doped PTFE (seed) undergoes a secondary growth method to form a molecular sieve membrane layer on the PTFE substrate membrane. The present invention can effectively promote the preparation of each molecular sieve membrane layer by limiting the temperature and time of the symbiosis of various molecular sieves, thereby effectively ensuring the successful preparation of each polycrystalline membrane.
[0037] In addition, the present invention also provides a deformable polycrystalline zeolite membrane prepared by the above method.
[0038] The beneficial effects of the present invention are:
[0039] The present invention adds nano zeolite to PTFE solution and PEO solution, and after being fully dispersed, the nano zeolite is spun on the PTFE substrate membrane by an electrostatic spinning process to obtain zeolite-doped PTFE (seed), and then the seed membrane is subjected to secondary growth to prepare a zeolite molecular sieve membrane, i.e., a polycrystalline zeolite membrane. The polycrystalline membrane prepared by this method has nanoparticles distributed in the zeolite molecular sieve membrane layer, which greatly improves the flexibility of the molecular sieve membrane layer and the binding force with the organic carrier, thereby making it compatible with the organic carrier, and also greatly reduces the interlayer defects between the molecular sieves, thereby greatly improving the separation selectivity of the membrane.
[0040] The method of the present invention can prepare a polycrystalline membrane that makes the mechanical properties of a brittle molecular sieve membrane layer and a flexible organic carrier compatible. The membrane is a deformable flexible membrane with extremely excellent tensile properties and elastic modulus. It is not easy to crack during actual use, which effectively improves the performance and service life.
[0041] The invention effectively overcomes the technical defect in the prior art that the synthesized zeolite molecular sieve membrane is very easy to crack due to the incompatibility of the mechanical properties of the flexible organic carrier and the brittle zeolite molecular sieve membrane layer.
[0042] In addition, the above-mentioned zeolite molecular sieve membrane has a simple preparation process, excellent separation performance, strong adaptability to organic carriers, and is easy to be industrially scaled up and applied. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is an optical photograph of a polycrystalline zeolite membrane;
[0044] Figure 2 is the X-ray diffraction pattern of the prepared PTFE / PTFE-MFI membrane;
[0045] Figure 3 is the X-ray diffraction pattern of the prepared PTFE / PTFE-FAU membrane;
[0046] Figure 4 is the X-ray diffraction pattern of the prepared PTFE / PTFE-NaA membrane;
[0047] Figure 5 This is a scanning electron microscope photo of the basement membrane PTFE;
[0048] Figure 6 is a scanning electron microscope photograph of the prepared PTFE-MFI membrane;
[0049] Figure 7 is a scanning electron microscope photo of the prepared PTFE-MFI (seed);
[0050] Figure 8 This is a scanning electron microscope photo of the MFI type molecular sieve;
[0051] Fig. 9 is a scanning electron microscope photograph of the prepared PTFE-FAU membrane;
[0052] Fig.10 is a scanning electron microscope photo of the prepared PTFE-FAU (seed);
[0053] Fig.11 This is a scanning electron microscope photo of FAU type molecular sieve;
[0054] Fig.12 is a scanning electron microscope photograph of the prepared PTFE-NaA membrane;
[0055] Fig.13 is a scanning electron microscope photo of the prepared PTFE-NaA (seed);
[0056] Fig.14 This is a scanning electron microscope photo of NaA molecular sieve;
[0057] Fig.15 This is the tensile test diagram of the prepared PTFE-MFI membrane / PTFE-FAU membrane / PTFE-NaA membrane. DETAILED DESCRIPTION
[0058] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the following.
[0059] Example 1
[0060] S1: Under normal temperature and pressure, MFI molecular sieve (particle size of 50-100 nm) is fully mixed with PTFE emulsion and PEO aqueous solution (the molar ratio of the three is 1:1:1) (mixing temperature is 25-30°C and time is 24h), and nano-zeolite is spun on the PTFE substrate membrane by electrospinning technology (electrospinning parameters are: voltage of 25kV, humidity of 50%, temperature of 25-30°C, and normal pressure) to obtain PTFE-MFI (seed);
[0061] S2 adds the secondary growth liquid of MFI type molecular sieve (including SiO2, NaOH, Al2(SO4)3·18H2O and H2O, wherein the molar ratio of the four is 0.02:0.01:0.0001:1.2) to the PTFE-MFI (seed), and obtains the PTFE-MFI membrane through symbiosis (the reaction temperature during symbiosis is 180°C and the time is 24h).
[0062] Among them, the X-ray diffraction patterns of PTFE substrate membrane and PTFE-MFI membrane are as follows Figure 2 As shown;
[0063] Scanning electron microscope pictures of PTFE-MFI membranes are shown in Figure 2. Figure 6 As shown;
[0064] Scanning electron microscope photo of PTFE-MFI (seed) Figure 7 As shown;
[0065] Scanning electron microscope photos of MFI molecular sieves are shown in Figure 8 shown.
[0066] Example 2
[0067] S1: Under normal temperature and pressure, FAU molecular sieve (particle size of 300-500nm) is fully mixed with PTFE emulsion and PEO aqueous solution (the molar ratio of the three is 1:1:1) (mixing temperature is 25-30℃, time is 24h), and nano zeolite is spun on the PTFE substrate membrane by electrospinning technology (electrospinning parameters are: voltage of 25kV, humidity of 50%, temperature of 25-30℃, under normal pressure) to obtain PTFE-FAU (seed);
[0068] S2: adding the secondary growth liquid of FAU type molecular sieve (including water glass, NaAlO2 and H2O; wherein the molar ratio of the three is 0.01:0.003:2.3) to the PTFE-FAU (seed), and obtaining the PTFE-FAU membrane through symbiosis (the reaction temperature during symbiosis is 100°C and the time is 48h).
[0069] Among them, the X-ray diffraction patterns of PTFE substrate membrane and PTFE-FAU membrane are as follows Figure 3 As shown;
[0070] Scanning electron micrograph of PTFE-FAU membrane Fig. 9 As shown;
[0071] Scanning electron microscope photo of PTFE-FAU (seed) Fig.10 As shown;
[0072] Scanning electron microscope photos of FAU molecular sieves Fig.11 shown.
[0073] Example 3
[0074] S1: Under normal temperature and pressure, NaA molecular sieve (particle size of 300-500nm) is fully mixed with PTFE emulsion and PEO aqueous solution (the molar ratio of the three is 1:1:1) (mixing temperature is 25-30°C, time is 24h), and nano zeolite is spun on the PTFE substrate membrane by electrospinning technology (electrospinning parameters are: voltage of 25kV, humidity of 50%, temperature of 25-30°C, under normal pressure) to obtain PTFE-NaA (seed);
[0075] S2: adding the secondary growth liquid of NaA molecular sieve (including LuDoxAs-40, Al, NaOH and H2O, wherein the molar ratio of the four is 0.07:0.01:0.6:7) to the PTFE-NaA (seed), and obtaining the PTFE-NaA membrane through symbiosis (the reaction temperature during symbiosis is 60°C and the time is 48h).
[0076] Among them, the X-ray diffraction patterns of PTFE substrate membrane and PTFE-NaA membrane are as follows Figure 4 As shown;
[0077] Scanning electron microscope pictures of PTFE-NaA membranes are shown in Figure 2. Fig.12 As shown;
[0078] Scanning electron microscope photo of PTFE-NaA(seed) Fig.13 As shown;
[0079] Scanning electron microscope photo of NaA molecular sieve Fig.14 shown.
[0080] In addition, the PTFE-MFI membrane, PTFE-FAU membrane, and PTFE-NaA membrane prepared in Examples 1-3 were bent respectively, and the optical photographs were as follows: Figure 1 As shown, it can be seen that the PTFE-MFI membrane, PTFE-FAU membrane and PTFE-NaA membrane prepared in the present invention all have bending properties and no cracking occurs.
[0081] The scanning electron microscope photos of the substrate membrane PTFE used in Examples 1-3 are as follows: Figure 5 shown.
[0082] The PTFE / PTFE-MFI (seed) / PTFE-MFI membrane in Example 1, the PTFE / PTFE-FAU (seed) / PTFE-FAU membrane in Example 2, and the PTFE / PTFE-NaA (seed) / PTFE-NaA membrane in Example 3 were subjected to tensile tests respectively. The test results are shown in FIG. Fig.15 shown.
[0083] pass Fig.15 It can be seen that the PTFE base membrane itself has good tensile properties. When the nano-molecular sieve particles MFI-type molecular sieve and NaA molecular sieve are introduced to make PTFE-MFI (seed) and NaA (seed), the tensile strength increases significantly; while the tensile strength of PTFE-FAU (seed) made of FAU-type molecular sieve decreases. The reason is that the nano-particle FAU-type molecular sieve>LTA-type molecular sieve>MFI-type molecular sieve.
[0084] In comparison, nano-molecular sieve materials of different sizes and morphologies have obvious changes in the tensile properties of the materials.
[0085] Elastic modulus: PTFE-MFI>PTFE-FAU>PTFE-NaA, among which PTFE-MFI has the best elastic modulus, which means that the material has high rigidity, is not easy to deform, and has stronger brittleness.
[0086] In addition, through Figure 2 Figure 3 Figure 4 It is shown that a dense molecular sieve membrane can be formed on the surface of the PTFE material as the organic substrate, which further illustrates that the present invention effectively overcomes the technical defect in the prior art that the prepared zeolite molecular sieve membrane is very easy to crack due to the incompatibility of the mechanical properties of the flexible organic carrier and the brittle zeolite molecular sieve membrane layer.
[0087] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a deformable polycrystalline zeolite membrane, characterized in that: The steps include: S1, at room temperature and pressure, fully mix the nano zeolite with the PTFE emulsion and the PEO aqueous solution, and use the electrospinning technology to spin the nano zeolite on the PTFE substrate membrane to obtain the zeolite-doped PTFE seed crystal; S2 adding a secondary growth solution of nano zeolite to the zeolite-doped PTFE seed crystals to obtain a molecular sieve membrane based on PTFE, i.e., the polycrystalline zeolite membrane, through symbiosis; In S1, the nano zeolite is an MFI type molecular sieve, a FAU type molecular sieve or an LTA type molecular sieve; When the nano zeolite is an MFI type molecular sieve, the zeolite-doped PTFE seed crystal is a PTFE-MFI seed crystal, and the molecular sieve membrane based on PTFE is a PTFE-MFI molecular sieve membrane; When the nano zeolite is a FAU type molecular sieve, the zeolite-doped PTFE seed is a PTFE-FAU seed, and the molecular sieve membrane based on PTFE is a PTFE-FAU molecular sieve membrane; When the nano zeolite is an LTA type molecular sieve, the selected molecular sieve is a NaA molecular sieve, the zeolite-doped PTFE seed crystals are PTFE-NaA seed crystals, and the molecular sieve membrane based on PTFE is a PTFE-NaA molecular sieve membrane.
2. The method for preparing a deformable polycrystalline zeolite membrane according to claim 1, characterized in that: In step S1, the molar ratio of the nano zeolite to the PTFE emulsion and the PEO aqueous solution is 1:(1-1.5):
1.
3. The method for preparing a deformable polycrystalline zeolite membrane according to claim 1, characterized in that: The process parameters of the electrospinning are as follows: The voltage is 25kV, the humidity is 50%, the temperature is 25-30℃, and the pressure is normal.
4. The method for preparing a deformable polycrystalline zeolite membrane according to claim 1, characterized in that: In step S1, the temperature during thorough mixing is 25-30° C. and the time is 24 h.
5. The method for preparing a deformable polycrystalline zeolite membrane according to claim 1, characterized in that: The particle size of the MFI molecular sieve is 50-100 nm; the particle size of the FAU molecular sieve is 300-500 nm; and the particle size of the NaA molecular sieve is 150-400 nm.
6. The method for preparing a deformable polycrystalline zeolite membrane according to claim 1, characterized in that: When the nano zeolite is an MFI type molecular sieve, the secondary growth liquid of the nano zeolite includes SiO2, NaOH, Al2(SO4)3·18H2O and H2O, wherein the molar ratio of the four is 0.02:0.01:0.0001:1.2; When the nano zeolite is a FAU type molecular sieve, the secondary growth liquid of the nano zeolite includes water glass, NaAlO2 and H2O; wherein the molar ratio of the three is 0.01:0.003:2.3; When the nano zeolite is NaA molecular sieve, the secondary growth liquid of the nano zeolite includes LuDoxAs-40, Al, NaOH and H2O, wherein the molar ratio of the four is 0.07:0.01:0.6:
7.
7. The method for preparing a deformable polycrystalline zeolite membrane according to claim 1, characterized in that: In step S2, when the nano zeolite is an MFI molecular sieve, the reaction temperature during the symbiosis is 180° C. and the reaction time is 24 h; When the nano zeolite is a FAU type molecular sieve, the reaction temperature during the symbiosis is 100°C and the time is 48h; When the nano zeolite is NaA molecular sieve, the reaction temperature during the symbiosis is 60° C. and the reaction time is 48 hours.
8. A deformable polycrystalline zeolite membrane, characterized in that: The deformable polycrystalline zeolite membrane is prepared by the method for preparing the deformable polycrystalline zeolite membrane according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method for supported ultrathin two-dimensional molecular sieve membrane and application of supported ultrathin two-dimensional molecular sieve film
CN109850913A
PTFE / CNT composite nanofiber membrane and preparation method thereof
CN113046927A